Stocking density affects transcriptome changes in the hypothalamic-pituitary-gonadal axis and reproductive performance in ducks - Hehe Liu; Xia Xiong; Fajun Pu; Jianmei Wang; Yanying Li; Yang Xi; Shengchao Ma; Lili Bai; Rongping Zhang; Li Liang; Chaowu Yang (Italian Journal of Animal Science, 2022)
The hypothalamic-pituitary-adrenal (HPA) axis and hypothalamic-pituitary-gonadal (HPG) axis plays a central role in mediating physiological responses related to the reproductive system under any stressful condition. However, the molecular mechanism underlying the effects of stress on physiology still needs to be elucidated. This study demonstrated that increasing the stocking density from 4 to 8 birds/m2 during the laying period decreased the egg production rate of laying ducks by 13.04 − 63.55% and feed intake by 7.40 − 23.44%. Transcriptome analysis between high- and low-feeding-density laying ducks revealed 469, 509, 428 and 210 differentially expressed genes (DEGs) in the hypothalamus, pituitary, ovary and follicular membrane, respectively. Gene ontology (GO) and KEGG enrichment analysis showed that the DEGs in the hypothalamus and pituitary were primarily enriched in the biostimulation and dopamine secretion pathways. The major enrichment pathways in the ovarian and follicular membranes involved lipid metabolism, negative regulation of inflammatory response, and steroid hormone biosynthesis. Among the DEGs in the HPG system, POMC and GnRH1 were identified, which may be manifesting their crucial roles in regulating the stress response and reproduction. Our data showed that a high stocking density as environmental stress negatively affects the reproductive performance in ducks through transcriptional changes in the HPG axis.Highlights Raising the stocking density from 4 to 8 birds/m2 decreased the egg production rate and feed intake in laying ducks. The transcriptome indicated that stocking density affects the stress response of laying ducks through the hypothalamus-pituitary. The stress signals are subsequently transmitted to affect gene expression related to the reproduction process in laying ducks’ ovarian and follicular tissues. The hypothalamic expression of POMC and GnRH1 may play a central role in integrating stress signals and the reproductive processes of laying ducks.